Preparation and evaluation of Spinacia oleracea extract and zinc Nanosizes effect on experimental biochemical disorders and oxidative stress in rat - Djouadi, Anfal (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
The main goal of this study was to evaluate nanotherapy based on ZnO nanoparticles and combination between phytotherapy and nanotherapy based on encapsulation of Spinach (Spinacia oleraceae) aqueous extract in nano vasicles to reverse fluoride overdose-induced- experimental biochemical disorders and oxidative stress in rats. For this purpose, thirty six male albino Wistar rats were randomly divided into 6 groups (n=6); the first group (G01) used as a control group. (G02) had given fluoride as fluoride sodium (NaF) in their drinking water to induce systemic toxicity (400 ppm) during 11 weeks. NaF rats injected intraperitoneally 03 times in the last 03 weeks by: Spinach Extract encapsulated in vesicles:7mg/kg body weight(G03), Spinach mediated ZnO nanoparticles green synthesis (SpE-ZnO-NPs): 7mg/kg body weight/week (G04) and Co-treatments (G03+G04) for NaF rats (G05) and control rats (G06). (G01) and (G02) were injected with physiological saline solution. Our biosynthesis ZnO using spinach extract (SpE-ZnO-NPs) characterized as irregular in the morphological shape, rod-like morphology with mean size 30 nm and hexagonal crystallites structure. In-vitro SpE-ZnO-NPs present anti-oxidant and anti-inflammatory and narrow antibacterial capacities without any In vivo toxicity at the concentrations studied indicating its safety and beneficial therapeutic effect. Spinach extract encapsulated vesicles characterized as regular (uniform in the morphological shape) and spherical with mean diameter 510 ± 27.5 nm. According to the results which have been obtained; fluoride exposure cause hyperthyroidism, hypoglycemia, hyperparathyroidism and anemia. Significant perturbation in markers functions of kidney (P<0.01) and liver (P<0.001). Results showed also a significant disturbance in electrolytes levels (P<0.01) in NaF group when compared to control rats. Moreover, the findings showed that overdose of fluoride affected antioxidant defense system by decreasing Glutathione (GSH) level and altering Glutathione S transferase (GST) and Glutathione peroxidase (GPx) activities simultaneously with malondialdehyde (MDA) level increase in brain, thyroid, liver, kidney, heart, spleen and testis tissues. The histological examination of the cellular structure of the testis, liver and kidney tissues of NaF exposed rats recorded remarkable changes in the tissues’ appearance. However, the administration of various treatments ameliorated thyroid function, hematological and biochemical parameters, and restored the histological alterations. Among these treatments, the combined treatment showed the greatest improvement in thyroid, renal, hepatic, hematological, and cardiovascular dysfunctions. It completely restored the studied biochemical parameters as well as that of oxidative stress. In conclusion, the present study demonstrated the beneficial effects of nano-phytotherapy, whether administered separately or in combination, on oxidative stress and its metabolic and physiological complications. الهدف الرئيسي من هذه الدراسة هو تقييم العلاج بالنانو بالاعتماد على الجسيمات النانوية ZnO والجمع بين العلاج النباتي والعلاج بالنانو اعتمادا على تغليف مستخلص السبانخ (Spinacia oleraceae) في حويصلات نانوية لتقليل الاضطرابات البيوكيميائية التجريبية والإجهاد التأكسدي المستحثين بمعاملة الفئران بتراكيز عالية من الفلور. لهذا الغرض، أجرينا دراستنا هذه على 36 فأر تم تقسيمهم إلى ست مجموعات في كل مجموعة ستة (06) فئران، المجموعة الأولى(G01) مجموعة شاهدة نظامها الغذائي عادي و مياه شربها خالية من أي إضافات تجريبية، المجموعة الثانية (G02) استحدث لديها تسمم عام وإجهاد تأكسدي تجريبيا بإعطائها الفلور على شكل ملح فلور الصوديوم (NaF) في ماء الشرب بتركيز 400 ملغ/ل مع نظام غذائي عادي لمدة 11 أسبوع. الفئران بعد تسميمها تم حقنها داخل الصفاق 3 مرات في آخر ثلاث أسابيع بـــ: حويصلات تحتوي مستخلص السبانخ بتركيز 7ملغ/كيلوغرام من وزن الجسم (G03) وجسيمات ZnO نانوية مصنعة بيولوجيا بواسطة مستخلص السبانج (SpE-ZnO-NPs) بتركيز 7ملغ/كيلوغرام من وزن الجسم (G04)، في حين أعطيت المجموعتين الخامسة (G05) والسادسة (G06) مزيــجًا من كل هذه العلاجات بنفس التراكيز وهي منفصلة حيث أن المجموعة (G06) فئران سليمة. تم حقن المجموعتين الأولى (G01) والثانية (G02) بالماء الفزيولوجي. تتميز جسيمات ZnO النانوية المحضرة طبيعيا باستخدام مستخلص السبانخ (SpE-ZnO-NPs) بأنها غير منتظمة في الشكل المورفولوجي، حيث أنها تشبه الأعواد بمتوسط حجم 30 نانومتر وهيكل بلوري سداسي. تُظهِر (SpE-ZnO-NPs) في المختبر فعالية مضادة للأكسدة ومضادة للالتهاب في حين أن الفعالية المضادة للبكتيريا ضعيفة، كما أنها لم تسبب تسمم في الجسم الحي عند التراكيز المدروسة مما يشير إلى أنها تراكيز آمنة ولديها تأثير علاجي فعال. تتميز الحويصلات نانوية الحاوية على مستخلص السبانخ بأنها منتظمة (انتظام الشكل المورفولوجي) وكروية بمتوسط قطر 510 ± 27.5 نانومتر. بناءً على النتائج التي تم الحصول عليها ؛ التعرض للفلورايد يؤدي إلى فرط نشاط الغدة الدرقية، نقص السكر في الدم، فرط جارات الدرقية وفقر الدم. اضطراب كبير في مؤشرات وظيفة كل من الكبد(P<0.001) والكلى(P<0.01) ، كما أظهرت النتائج وجود اضطراب معنوي في مستويات الشوارد(P<0.01) في أمصال المجموعة المستحدث لديها التسمم بالفلورايد (NaF) مقارنة بالمجموعة الشاهدة. بالإضافة إلى هذا، أظهرت النتائج أيضا أن التسمم بالفلورايد يؤثر على الأنظمة المضادة للإجهاد التأكسدي بتخفيض مستويات الغلوتاثيون(GSH) وتثبيط نشاط الإنزيمين (GST) و(GPx) بالتزامن مع رفع مستويات النواتج الثانوية لأكسدة الدهون (MDA) في نسيج كل من الدماغ، الغدة الدرقية، الكبد، الكلية، القلب، الطحال والخصية. المعاينة النسيجية للبُنـــَى الخلوية لنسيج كل من الخصية، الكبد والكلية لدى المجموعة المستحدث لديها التسمم بالفلورايد (NaF) أظهرت تشوهات واضحة على مستوى مظهر الأنسجة. من جهة أخرى سجلنا أن حقن مختلف العلاجات منفصلة أو ممتزجة حسَّن في معايير عمل الغدة الدرقية، معايير الدم، المعايير البيوكيميائية وكذا في البُنـــَى النسيجية للأعضاء المدروسة، بينما أعطى مزيج كل هذه العناصر العلاجية أفضل النتائج من حيث تحسن وظائف الغدة الدرقية، الكلى، الكبد، القلب وفقر الدم والذي أدى إلى استعادة كاملة للمعايير البيوكيميائية، للبُنـــَى النسيجية قيد الدراسة وللإجهاد التأكسدي. أخيرا، بينت هذه الدراسة فوائد دمج كل من العلاج النباتي والنانوي بشكل منفصل أو مجتمعة على الإجهاد التأكسدي ومضاعفاته الأيضية والفسيولوجية.
أطروحة دكتوراه تخصص يوكيمياء تطبيقية في العلوم الطبيعة و الحياة
Keywords: Spinacia oleraceae, Nano vesicles, ZnO nanoparticles, Fluoride, Oxidative stress; السبانخ (Spinacia oleraceae)، حويصلات نانوية، جسيمات ZnO نانوية، ، فلورايد، إجهاد تأكسدي